2020
DOI: 10.1002/fsn3.1393
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and mineral contents of Lycium ruthenicum Murr. and antioxidant activity against isoproterenol‐induced acute myocardial ischemia in mice

Abstract: Dried fruits of black goji were investigated for their fatty acid, mineral contents, and antioxidant activity against isoproterenol‐induced acute myocardial ischemia in mice was revealed. It was observed that the key fatty acids from Lycium ruthenicum Murr. (LRM) oil studied included linoleic (59.38%), oleic (20.85%), palmitic (7.07%), linolenic (2.98%), and stearic acids (5.31%), which together comprised 95.59% of the total fatty acids. The key mineral nutrients studied were potassium (17,631.15 mg/kg), calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The most abundant fatty acids were linoleic (C18:2n-6), oleic (C18:1n-9), palmitic (C16:0), and stearic (C18:0) acid, accounting for about 95% of total fatty acids. Similar results were reported for red goji berry cultivated in Italy [40,41], Greece [42], Turkey [43], North Macedonia [44] and for Chinese black goji berries [24,45]. Table 2.…”
Section: Red Goji Yellow Goji Black Gojisupporting
confidence: 84%
See 1 more Smart Citation
“…The most abundant fatty acids were linoleic (C18:2n-6), oleic (C18:1n-9), palmitic (C16:0), and stearic (C18:0) acid, accounting for about 95% of total fatty acids. Similar results were reported for red goji berry cultivated in Italy [40,41], Greece [42], Turkey [43], North Macedonia [44] and for Chinese black goji berries [24,45]. Table 2.…”
Section: Red Goji Yellow Goji Black Gojisupporting
confidence: 84%
“…The analysis was performed by inductively coupled plasma optical emission spectrometry (ICP-OES) using a Thermo Scientific iCAP 6500 Duo (Thermo Fisher Scientific, Cambridge, UK) after microwave digestion described by Yossa Nzeuwa et al [24]. Mineral contents were quantified against standard solutions of known concentrations, which were analyzed simultaneously, and results were expressed as mg per 100 g of fresh goji berry fruits.…”
Section: Mineral Compositionmentioning
confidence: 99%
“…Catechins and other phenolic compounds can normalize lipid peroxidation and alleviate adriamycin-induced oxidative stress in rats [ 86 ]. Studies have shown that lycium berry polyphenols can increase the expression of antioxidant enzymes such as catalase, heme oxygenase-1, glutathione peroxidase, and SOD, as well as reduce the oxidative stress of lipopolysaccharide (LPS) stimulated acute lung injury mice [ 87 ].…”
Section: Molecular Mechanisms Related To the Antioxidant Effect Of Lbpsmentioning
confidence: 99%
“…Both black goji berry seed and flesh oil are sources of polyunsaturated fatty acids. They contain saturated, monounsaturated, and polyunsaturated fatty acids in which linoleic, oleic, and palmitic acids are predominant . K, Na, P, Ca, and Mg are the five most abundant minerals in black goji berry, whereas Co, Cr, Cu, Li, Mn, P, Ti, V, B, Si, and Zn are also present in trace amounts .…”
Section: Introductionmentioning
confidence: 99%